Hi, f(t) = t Cos w t f '(t) = f ''(t) = Can someone help quick please and tell me how to get the the answers and what rule it is! thanks
Follow Math Help Forum on Facebook and Google+
I think i have worked it out now! Product rule?! f '(t) = Coswt - wtsinwt f ''(t) = ?!?!?!?!
Originally Posted by madcal87 I think i have worked it out now! Product rule?! f '(t) = Coswt - wtsinwt f ''(t) = ?!?!?!?! Hello, 1. you used product rule and chain rule - and your result is OK 2. Use chainrule on the first summand and product rule and chain rule on the second summand. I've got:
for f ' (t) i used the product rule ! Can u give me a step by step of f '' (t) please.... because im confused!
Originally Posted by madcal87 for f ' (t) i used the product rule ! Can u give me a step by step of f '' (t) please.... because im confused! Hi, Ok here we go: Your result: Expand the bracket and collect like terms.
View Tag Cloud